Short communication. Changes in the composition of sows'milk between days 5 to 26 of lactation - Daza, A.=700 1 Rioperez, J.; Centeno, C.
(Es, En)
ilus., 21 ref.
Keywords: CERDAS; LECHE; EVOLUCION; CONTENIDO DE MATERIA SECA; CONTENIDO PROTEICO; VALOR ENERGETICO; ESPAÑA; COMPOSICION DE LA LECHE; CONSTITUYENTES